The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fchem.2021.740421
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Bis-Amide Matrine-type Alkaloids From Sophora alopecuroides With Anti-inflammatory Effects

Abstract: Four new alkaloids (1–4) belonging to rare examples of bis-amide matrine-type were isolated from the seeds of sophora alopecuroides. Their structures including absolute configuration were determined by extensive spectroscopic analysis, electronic circular dichroism (ECD) interpretation, and X-ray diffraction crystallography. Chemically, bis-amide matrine-type alkaloids can provide new molecular template for structural modification. Compounds 3–4 displayed obvious anti-inflammatory effects based on the inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is well known that inflammatory cytokines are important indicators of the immune response in animals; they mediate T, B and other cell activation, proliferation and differentiation and play important roles in the inflammatory response. SA alkaloids inhibited the LPS-induced secretion of proinflammatory cytokines, such as IL-6 and TNF-α, in rats in a dose-dependent manner [38,39], suggesting that SA alkaloids have an inhibitory effect on the inflammatory responses caused by LPS stimulation. Liang et al [40] also reported that, compared with those in the LPS model group, the pathological injury to lung and kidney tissues was reduced to different degrees and that the serum NO, TNF-α, and BUN levels were decreased.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that inflammatory cytokines are important indicators of the immune response in animals; they mediate T, B and other cell activation, proliferation and differentiation and play important roles in the inflammatory response. SA alkaloids inhibited the LPS-induced secretion of proinflammatory cytokines, such as IL-6 and TNF-α, in rats in a dose-dependent manner [38,39], suggesting that SA alkaloids have an inhibitory effect on the inflammatory responses caused by LPS stimulation. Liang et al [40] also reported that, compared with those in the LPS model group, the pathological injury to lung and kidney tissues was reduced to different degrees and that the serum NO, TNF-α, and BUN levels were decreased.…”
Section: Discussionmentioning
confidence: 95%
“…The inhibitory effects of compounds 41-44 on TNF-α and IL-6 in LPS-stimulated RAW264.7 cells were evaluated [50]. The results showed (Table 1) that compounds 43 and 44 have obvious anti-inflammatory effects in a dose-dependent manner.…”
Section: -44mentioning
confidence: 99%